EFISIENSI LAYOUT RAWAT JALAN RS HARAPAN MAGELANG - , Etta Evita Chesario, Agastya, SE., MBA., MPM. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: RS Harapan is a C-typed private hospital at kotamadya Magelang since 1992, initially was a foundation called Wijaya Kusuma Foundation and later on became a limited named PT Sinar Harapan keluarga. The outpatient department in RS Harapan is physically inefficient regarding the scattered room that are not functionally grouped. It causes long walking distance for all patients, physicians, and administrative staff. Objective: to acknowledge whether the existing layout is physically efficient yet to identify a better and more efficient outpatient department layout. Method: this was a month study case carried out at outpatient departments at RS Harapan Magelang. Result: the results of the analysis over the existing layout depicted that the total movement of people walking between the rooms in outpatient department at RS Harapan was initially 6443 meter, yet the total movement of the proposed layout using POM for Windows software significantly decreased up to 72.56 percent becoming a mere 1768 meter. The ambulatory care moved to room 4, radiology to room 3, laboratory to room 2, pharmacy to room 5, physiotherapy to room 1. Considering the zonation theory, writer had a secondary opinion that none of the outpatient room need to be allocated. Instead of the ambulatory care and the physiotherapy room, they significantly in a need of allocation to room 5 and room 1. Conclusion: the existing layout of outpatient department in RS Harapan is inefficient since the comparison of outpatient rooms distances over physical movement between the ambulatory care and ancillaries department was unproportionate. The efficient outpatient layout according to analysis result using POM for Windows software was by allocating the ambulatory care department to room 4, radiology department to room 3, laboratory department to room 2, pharmacy department to room 5 and physiotherapy department to room 1. Besides, writer had a secondary opinion over an efficient outpatient layout which was to allocate none of the departments except the ambulatory care department and physiotherapy department to room 5 and 1.